(untitled) (Research, Society and Development, 2025)
Systemic arterial hypertension is characterized by high levels of systolic blood pressure and diastolic blood pressure, exceeding BP, with a standard value equal to 120/80, capable of causing damage to the heart, brain, and kidneys. Non-modifiable hereditary factors, such as family history, damage to endothelial mechanisms, narrowing blood vessels, veins and arteries, suggest deleterious effects, causing a reduction in the production of vasodilators, such as nitric oxide and L-arginine. On the other hand, modifiable factors acquired in advanced stages of the life cycle, associated with smoking, alcoholism, nutritional diet, and socioeconomic conditions. This article aims to address hypertension, hemodynamic effects and aging through a literature review. Therefore, some studies by eligibility criteria are part of this review, as they address the efficiency of PE in stabilizing BP, as a hemodynamic response. For this, 154 articles were consulted,13 by the eligibility criteria, with dates between 2018 and 2024, in the databases: BVS, Lilacs, Cielo, JCR, Bireme, PubMed, Scopus, and Pedro. As a result, the effects of PE constituted a stabilizing mechanism of BP, up to 48 hours.